Computational determination of coordination structure impact on adsorption and acidity of pristine and sulfated MOF-808. Issue 13 (5th May 2021) - Yang, Bo; Wheeler, Joshua I.; Sorensen, Brett; Steagall, Robert; Nielson, Taylor; Yao, Jianhua; Mendez-Arroyo, Jose; Ess, Daniel H.
Abstract : Metal–organic frameworks (MOFs) are composed of metal nodes connected by organic linkers. Abstract : Metal–organic frameworks (MOFs) are composed of metal nodes connected by organic linkers. With the massive amount of possible metal and linker combinations, it is critical to develop structure–property relationships. However, a major impediment to developing these relationships is that MOFs often have multiple metal coordination structures in a single crystal. Here, we report periodic and cluster density functional theory (DFT) calculations analyzing the coordination structures of MOF-808 and sulfated MOF-808 and their physical and chemical properties. For MOF-808, we determined coordination structures by comparing computationally determined lattice constants with experimental values and then used these coordination structures to simulate N2 and Ar adsorption isotherms. Our simulated average N2 and Ar uptakes agree very well with the experimental values. For the sulfated MOF-808, which has been proposed to be a superacidic material, we determined the impact of coordination structure on acidity. Surprisingly, our results based on calculated proton affinities suggest a 10 25 range in acid site strength depending on the coordination structure, with only a few sites having high acidity. The use of vibrational frequencies and other property-based methods for determining relative acidity fail. Our analysis revealed that the acidity of sulfated MOF-808 is unlikely controlled by a sulfate–water hydrogen bond that was previously proposed. Instead, we show that there is a strong correlation between conjugate base stability and proton affinity to rationalize acidity of protons in a single coordination structure model as well as across all coordination structures.